Economic growth, renewable and nonrenewable electricity consumption: A fresh evidence from a panel sample of African countries - Delphin Kamanda Espoir; Regret Sunge; Frank Bannor (ZBW - Leibniz Information Centre for Economics, 2021)
Energy transition has imposed a policy priority dilemma between economic growth and global warming mitigation. Existing studies in Africa have examined the impact of energy sources on growth but overlooked the differences across countries and regions. This study seeks to achieve two research objectives. First, it examines and compares the impact of renewable electricity consumption (REC) and nonrenewable electricity consumption (NREC) on growth in 48 African countries between 1980 and 2018. The study uses the recent panel estimators of cross-sectional dependence, slope heterogeneity, and cointegration. For the short and long-run marginal effects, the Pooled Mean Group estimator is used. Second, the analysis is extended to account for the heterogeneous effects of energy among African countries in four regional economic communities (EAC, COMESA, SADC, and ECOWAS). Here, we use the random-coefficients linear regression and kernel-based regularized least squares machine learning algorithm. The findings are as follows: (1) there is cointegration amongst the variables, (2) for the entire sample, both REC and NREC have positive and significant effects on growth, but NREC has an enormous impact, (3) the marginal effects of REC and NREC differ across African regions. Given the energy transition dilemma, there is a need for public-private partnership investments to bring a balanced mix between NREC and REC. Also, the heterogeneity suggests that a one-size-fit-all policy designed to increase growth through REC may not yield the same outcome in Africa. Therefore, while policies should speak to the common global agenda, there is a need to internalise and localise the strategies in each country and/or region.
Keywords: O47; O55; Q42; Q54; 330; Renewable energy consumption; Economic growth; Climate change; Africa